Adult Learner-centered Institutions: Best Practices for the 21st Century - Susan Mancuso (Adult Education Research Conference, 2000)
Adult student enrollment in higher education is approaching 50%, yet most college practices have been designed for younger, traditional age students. This study uses a benchmarking research methodology, including surveys and site visits, to identify best practices at selected adult centered institutions. The findings were distilled into one overarching theme and thirteen related themes.